A heart for freedom the remarkable journey of a young dissident, her daring escape, and her quest to free China's daughters - Chai, Ling (Carol Stream, Ill. Tyndale House Publishers, 2011)
"A Heart for Freedom is a tale of passion, political furor, and spirtual awakening. An inside look at China, then and now. A love song to a now forbidden country. And the inspirational true story of a woman who has dedicated everything to giving people in China their chance at a future."--P. [4] of jacket.
Daughter of China -- Tiananmen Square -- Farewell to Beijing -- The American dream meets Chinese reality -- Freedom calling.
Keywords: Chai, Ling; Christian converts -- China -- Biography; China -- Politics and government -- 2002-.; China -- Politics and government -- 1976-2002.